Analysis Type of Theme in the Introduction Sections of English Study Program Students Research Proposals Mahasaraswati Denpasar - I Made Arya Dinata Kusumantara; I Made Yogi Marantika (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
The study concentrates mainly on the various themes and rheme styles used in the introduction section of students' research proposals for the English study program at Mahasaraswati Denpasar. The study's objective is to look at the variety of themes and rhemes used in introduction paragraphs. The study used a qualitative method with a descriptive design to analyze the data. The information was taken from five research proposals from students who are studying English. Halliday's (1994, 2004) theory was applied to the data in order to analyze the theme and rheme. In five introduction sections of research proposals for English study programs, the most prevalent type appeared 36 times. In contrast, the introduction section of students' research proposals for English study programs contains five instances of the topical theme